Decision Support System for the Verification Process of Civil Servant Promotion Proposals in the Bojonegoro Regency Government Using the Analytic Hierarchy Process (AHP) Method - Resty Alfianda Zellyanawati; Tanhella Zein Vitadiar (Journal of Engineering, Electrical and Informatics, 2025)
The advancement of information technology has significantly transformed governance practices, particularly in enhancing efficiency, transparency, and accountability in public service delivery. One of the critical aspects of civil service management is the promotion of Civil Servants (PNS), which serves as a form of recognition for performance and dedication to the state. Following regulatory changes, especially the enactment of BKN Regulation Number 4 of 2023, the promotion schedule has increased to six times a year, demanding a faster and more accurate verification process. Although the State Civil Apparatus Information Sistem (SIASN) is currently used to support administrative procedures, the verification process for promotion proposals remains manual and limited to specific administrators. Therefore, this study aims to design a Decision Support Sistem (DSS) using the Analytical Hierarchy Process (AHP) method to assist in the objective and sistematic verification of promotion proposals. AHP was chosen for its ability to incorporate both qualitative and quantitative aspects while minimizing subjective bias in decision-making. The proposed DSS considers criteria such as length of service, performance evaluation, educational background, and disciplinary history. This sistem successfully the verification process and supports more transparent and accurate decision-making within the Government of Bojonegoro Regency .